1967
DOI: 10.1103/physrev.153.1287
|View full text |Cite
|
Sign up to set email alerts
|

Decay ofPr137

Abstract: A praseodymium isotope with a half-life of 75 min has been assigned to 137 Pr. It decays with a iC-captureto-positron ratio of 2.5±0.2 and a maximum positron energy of 1.74±0.05 MeV. Approximately 6% of the disintegrations are to excited states of 137 Ce. The energies and intensities of 28 gamma-ray transitions were measured with a Ge(Li) detector. Coincidences of the gamma rays were measured using two 3-in. Nal(Tl) crystals and a multiparameter analyzer. An energy-level diagram consistent with the observed ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1972
1972
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Information about the low-spin excited states of the obtained from decay studies [1][2][3][4] and from neutron pick-up reactions performed for the N = 81 nuclei [5,6]. These investigations have shown that in these nuclei the lowest states with spins and parities 3/2 + , 1/2 + and 11/2-are predominantly neutron singlehole states.…”
Section: Introductionmentioning
confidence: 99%
“…Information about the low-spin excited states of the obtained from decay studies [1][2][3][4] and from neutron pick-up reactions performed for the N = 81 nuclei [5,6]. These investigations have shown that in these nuclei the lowest states with spins and parities 3/2 + , 1/2 + and 11/2-are predominantly neutron singlehole states.…”
Section: Introductionmentioning
confidence: 99%